Disparities in Risks of Inadequate and Excessive Intake of Micronutrients during Pregnancy. Issue 11 (7th September 2021) - Sauder, Katherine A; Harte, Robyn N; Ringham, Brandy M; Guenther, Patricia M; Bailey, Regan L; Alshawabkeh, Akram; Cordero, José F; Dunlop, Anne L; Ferranti, Erin P; Elliott, Amy J; Mitchell, Diane C; Hedderson, Monique M; et al.
ABSTRACT: Background: Inadequate or excessive intake of micronutrients in pregnancy has potential to negatively impact maternal/offspring health outcomes. Objective: The aim was to compare risks of inadequate or excessive micronutrient intake in diverse females with singleton pregnancies by strata of maternal age, race/ethnicity, education, and prepregnancy BMI. Methods: Fifteen observational cohorts in the US Environmental influences on Child Health Outcomes (ECHO) Consortium assessed participant dietary intake with 24-h dietary recalls ( n  = 1910) or food-frequency questionnaires ( n  = 7891) from 1999–2019. We compared the distributions of usual intake of 19 micronutrients from food alone (15 cohorts; n  = 9801) and food plus dietary supplements (10 cohorts with supplement data; n  = 7082) to estimate the proportion with usual daily intakes below their age-specific daily Estimated Average Requirement (EAR), above their Adequate Intake (AI), and above their Tolerable Upper Intake Level (UL), overall and within sociodemographic and anthropometric subgroups. Results: Risk of inadequate intake from food alone ranged from 0% to 87%, depending on the micronutrient and assessment methodology. When dietary supplements were included, some women were below the EAR for vitamin D (20–38%), vitamin E (17–22%), and magnesium (39–41%); some women were above the AI for vitamin K (63–75%), choline (7%), and potassium (37–53%); and some were above the UL for folic acid (32–51%), iron (39–40%), and zinc (19–20%). Highest risks for inadequate intakes were observed among participants with age 14–18 y (6 nutrients), non-White race or Hispanic ethnicity (10 nutrients), less than a high school education (9 nutrients), or obesity (9 nutrients). Conclusions: Improved diet quality is needed for most pregnant females. Even with dietary supplement use, >20% of participants were at risk of inadequate intake of ≥1 micronutrients, especially in some population subgroups. Pregnancy may be a window of opportunity to address disparities in micronutrient intake that could contribute to intergenerational health inequalities.